Paving our path - Ezihaslinda, Ngah (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
5 June 2010. Working towards a new faculty while simultaneously planning to offer four new programmes is not an easy path. Since the very first day, everybody seemed to foresee a long and winding road that lies ahead. Nevertheless, enlightened with the belief ‘a trouble shared is a trouble halved’, every effort was executed particularly towards the completion of the required documents. Led by our visionary Dean, Professor Dr. Abd Jalil Borham and assisted by Deputy Dean of Academic Affairs, Munira Razak, the team is progressing according to the plan.